Legal Research Methods in Islamic Education: Normative, Empirical, and Contextual Analysis - Muhammad Setiawan; Achmad Sulton (Classroom: Journal of Islamic Education, 2026)
This article aims to examine legal research methods in Islamic education through normative, empirical, and contextual analysis. Islamic education, as an interdisciplinary field of study, requires a methodological approach capable of bridging Islamic legal norms, the realities of educational practice, and the surrounding social context. This research employs a qualitative approach with library research. Data were obtained from primary sources, including the Quran, Hadith, Islamic education laws and regulations, and secondary sources, including books and articles from reputable national and international journals. The results of the study indicate that normative legal research plays a role in examining the legal and normative foundations of Islamic education, empirical legal research serves to examine the implementation of Islamic educational law in social practice, while a contextual approach enables adaptive legal interpretation to societal dynamics. The integration of these three approaches produces a comprehensive and relevant methodological framework for the development of contemporary Islamic education.